The coronavirus pandemic: Psychosocial burden, risk-perception, and attitudes in the Austrian population and its relation to media consumption - Schabus, Manuel; Eigl, Esther-Sevil; Widauer, Sebastian Stefan (Frontiers in Public Health, 2022)
Objective. The aim was to assess the knowledge and attitudes regarding the coronavirus pandemic in the Austrian general population after the second infection wave in Austria. Methods. A self-designed questionnaire was available online from 17th January to 19th February 2021. Knowledge, attitudes, fears, and burdens were collected in a sample of 3848 adults in the Austrian general population. Results. 67.2% reported their greatest fear was that a close relative could be infected; the fear of dying from corona virus oneself, however, was mentioned least frequently (15.2%). Isolation from family and friends (78%), homeschooling for parents (68.4%), and economic consequences (67.7%) were perceived as most stressful. Personal risk for COVID-19-associated (ICU) hospitalization was overestimated 5- to 193-fold depending on age group, and back then 40.8% of the sample did not expect a return to normality before 2022. Depending on the media mainly consumed, the sample could be divided into two subsamples whose estimates were remarkably opposite to each other. Conclusion. The results show a high degree of psychosocial burden and distress in the Austrian population and emphasize the need for more objective risk communication in order to counteract individually perceived risk and consequently anxiety. Altogether data call for a stronger focus and immediate action for supporting mental well-being and general health in the aftermath of the Corona pandemic.